Spontaneous haemopneumothorax: are guidelines overdue?. Issue 3 (1st May 2002) - Hart, S R; Willis, C; Thorn, A; Barfoot, L
Abstract : Spontaneous life threatening haemopneumothorax is an unusual but treatable cause of unexpected circulatory collapse in young patients. Two case histories are presented to illustrate the management of this condition. Diagnosis and initial management depends on early recognition of the clinical pattern by accident and emergency (A&E) staff and/or hospital physicians. Problems may arise for two reasons. Firstly, as the incidence of life threatening spontaneous haemopneumothorax is low, admitting medical staff may not have experienced this condition in the absence of trauma. Secondly, unlike surgeons, staff in these specialties are unlikely to have received training of either traumatic or spontaneous haemopneumothorax. The cases illustrate potential problems. Not only early recognition of the clinical pattern but also proactive intervention in the A&E department are necessary before referral to a cardiothoracic surgeon. Furthermore, we suggest treatment would be improved by the introduction of management guidelines.